Analisis Kepatuhan Kunjungan Antenatal Care (ANC) di UPTD Puskesmas Tanjung Agung Kabupaten Ogan Komering Ulu - Luciana; Chairil Zaman; Arie Wahyudi (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The main targets of the SDGs are related to reproduction and maternal health. Many women die during pregnancy and childbirth. Every pregnancy has a risk of facing maternal death. One way to suppress MMR and IMR is Antenatal Care. The purpose of this study was to look at the factors associated with adherence to Antenatal Care visits. This study uses a quantitative method with a Cross Sectional approach. Statistical test using Chi Square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is a relationship between age (p = 0.015; OR = 4.438), education (p = 0.005; OR = 4.693), the role of cadres (p = 0.008; OR = 4.331) with Antenatalcare at the UPTD Puskesmas Tanjung Agung, Ogan Komering Regency. Ulu 2021. There is no employment relationship (p= 0.379). information media (p= 1,000) and service facilities (p= 1,000) with antenatal care at UPTD Puskesmas Tanjung Agung, Ogan Komering Ulu Regency in 2021. The most dominant variable is the role of cadres (p= 0.002; OR= 8.129). Suggestions to the Tanjung Agung Public Health Center, the findings of this study can be used by the OKU District Health Office in order to increase the role of cadres in inviting pregnant women to check their pregnancies according to the rules.